2019
DOI: 10.1016/j.neuro.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Do you feel it now? Route of administration and Δ9-tetrahydrocannabinol-like discriminative stimulus effects of synthetic cannabinoids in mice

Abstract: A recent push to provide more translationally relevant preclinical models for examination of pharmacological mechanisms underlying inhaled substances of abuse has resulted in the development of equipment and methods that allows exposure of freely moving rodents to aerosolized psychoactive drugs. In the present study, synthetic cannabinoids (CP55,940, ABCHMINACA, and AMB-FUBINACA) were administered intraperitoneally (i.p.) or aerosolized via a modified electronic cigarette device. Subsequently, the compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 42 publications
(65 reference statements)
3
6
0
Order By: Relevance
“…Accordingly, previous studies also showed sex differences in tetrad behaviors induced by THC 42,43 . In addition, the sex‐biased impact of MMB‐Fubinaca has recently started to be evaluated 36 . Our results show a higher sensitivity for MMB‐Fubinaca in male than in female mice, at both behavioral and synaptic levels.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Accordingly, previous studies also showed sex differences in tetrad behaviors induced by THC 42,43 . In addition, the sex‐biased impact of MMB‐Fubinaca has recently started to be evaluated 36 . Our results show a higher sensitivity for MMB‐Fubinaca in male than in female mice, at both behavioral and synaptic levels.…”
Section: Discussionsupporting
confidence: 77%
“…MMB‐Fubinaca intoxication in mouse models has been shown to induce cannabinoid‐like behavioral effects such as seizures, hypolocomotion, or hypothermia 3,6,24,28,29,35 . Interestingly, a sex‐dependent effect of MMB‐Fubinaca has been described to be blocked by CB 1 antagonists in a paradigm assessing addictive‐like behavior 36 . However, previous studies only used pharmacological tools and did not address CB 1 dependency by using specific mutant mice lacking CB 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…26 Evaluation of abuse liability of substances via ip administration is comparable to vapor inhalation. 27 This study was to investigate the effects of systemic administration with THC, the major component in cannabis, on mouse retinas and its underlying mechanisms. For the first time, we explored the effects of dosing and administration duration (up to 2 months) that reflect cannabis abuse situations, complementing studies into the mechanisms underlying retina damage caused by cannabis abuse.…”
Section: Discussionmentioning
confidence: 99%
“…injection. Wiley et al (2015), Lefever et al (2017), andWiley et al (2019) all used doses ranged between 0.03 mg/kg and 3 mg/kg. All these studies showed full THC substitution by AB-CHMINACA and produced the tetrad effect (decreased motor activity, decreased temperature, catalepsy, and antinociception which means decrease the sensation to painful stimuli).…”
Section: Discussionmentioning
confidence: 99%